Radar Target Complex High-Resolution Range Profile Modulation by External Time Coding Metasurface - Yu, Shijian; Guan, Dongfang; Gu, Ziyang; Guo, Jinxing; Liu, Zhen; Liu, Yongxiang (IEEE transactions on microwave theory and techniques, 2024)
In this article, we propose a method based on time coding metasurface (TCM) to modulate the characteristics of radar targets in complex high-resolution range profiles (HRRPs). Unlike the existing works where metasurfaces are typically attached to target surfaces, in our work, the metasurface and controlled target are separable, making modulation more flexible. The proposed method involves controlling the equivalent scattering phase of distance offset false targets within the HRRP, which are generated through TCM by adjusting the modulation parameters. The scattering characteristics of the false target and the controlled target are combined within the same distance unit to create a superimposed scattering feature vector. By taking into account the influence of interference effect, we are able to modulate the scattering characteristics of radar targets within the complex HRRP. The proposed method was validated through theoretical analysis, simulation experiments, and actual experiments conducted in various scenarios. The experimental results demonstrate that the false targets generated by the external TCM can be used to enhance or weaken the scattering intensity of the original target in HRRP, thereby changing the overall image characteristics and posing challenges to target recognition. This method can achieve the modulation of radar target image characteristics under noncoverage conditions, expanding the application scenarios of metasurfaces in the field of radar electronic countermeasures (ECM).